The Effect of Breast Massage Training to Mothers on the Exclusive Breastfeeding Rate and Its Problems in Mothers during the Neonatal Period - Ramezani 1, Somayeh; Bolbolhaghighi 2, Nahid; Kolahdozan 1, Sakineh; Khosravi 3*, Ahmad (Shahroud Journal of Medical Sciences, 2018)
Background: Breast massage helps the mother relax, causing the secretion of oxytocin hormone. This makes the milk flow rapidly. The aim of this study was to examine the impact of breast massage training on reducing problems of breastfeeding in mothers and increasing the rate of exclusive breastfeeding.Methods: This was a randomized clinical trial performed on 132 nulliparous women after childbirth. The participants were randomly divided into breast massage and control groups. Different methods of breast massage were trained to the intervention group before each breastfeeding and to the control group (routine training in breastfeeding after delivery) as well. Then, the questionnaires on breastfeeding and breastfeeding problems were completed by both groups on the 28th dat after the childbirth.Results: The intervention group mean age was 25.5±4.52 based on the results and the mean age in the control group was calculated as 26.3±4.9. No significant difference was found between the groups regarding the demographic characteristics, suggesting the comparability of the two groups. However, we found a significant difference in the breastfeeding problems between the two groups (P<0.05). The rate of exclusive breastfeeding in the intervention and control groups was measured as 54.5% and 45.5%, respectively. These values were not found to be statistically significant (P<0.05). Employing descriptive statistics, chi-square test, and ANOVA and using the SPSS software, we analyzed the resulting data.Conclusions: Demonstrated by the study results, massage training can lead to reduced breastfeeding-related problems. In addition, due to limited number of studies on this topic, we suggest to do more research on the effect of breast massage on breastfeeding and its beneficial.